The Influence of the Blended Learning Model on Students Digital Learning : Meta-Analysis - Komari Komari; Dewanto Dewanto; Tomi Apra Santosa; Yusak Noven Susanto; , Dewi Maharani Rachmaningsih (Edumaspul: Jurnal Pendidikan, 2023)
Blended learning model research has been widely carried out in the world of education, but no meta-analysis of blended learning models has been found on students' digital literacy. This research aims to determine the effect of the blended learning model on students' digital literacy. This research is a type of meta-analysis research. This research analyzes 11 effect sizes sourced from Google Scholar, ERIC, ScienceDirect and Wiley from 2019-2023 which includes 220 students. Data analysis with the help of the JSAP application. This research concludes that the summary effect size value obtained from the random effect model is 0.793 with medium criteria. These findings show that the blended learning model can have a significant influence on students' digital literacy.